2013
DOI: 10.1111/faf.12038
|View full text |Cite
|
Sign up to set email alerts
|

The decline of Steller sea lions (Eumetopias jubatus) in the North Pacific: insights from indigenous people, ethnohistoric records and archaeological data

Abstract: A number of hypotheses have been proposed to explain the most recent decline (1977–2012) of Steller sea lions (SSL; Eumetopias jubatus) in the Gulf of Alaska and Aleutian Islands. We examined hypotheses about fisheries competition, environmental change, predation, anthropogenic effects and disease using observations of modern Aleut and archaeological, ethnohistoric and ethnographic data from the western Gulf of Alaska and Aleutian Islands. These data indicate that Steller sea lion numbers have declined and rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 84 publications
1
12
0
Order By: Relevance
“…Concurrent with the decline of sea lions and expansion of groundfish fisheries in the Aleutians in the late 1970s, there was a substantial change in ocean climate and declines in the abundance of non-fished species such as capelin, skates and benthic invertebrates [ 88 ]. Thus while commercial fisheries might be evoked to partially explain the interannual fluctuations in the abundance of some species [ 89 ], the geographic and temporal coherence of the collapse of large numbers of taxa argues for a large-scale common cause such as changes in ocean climate [ 45 , 89 – 91 ].…”
Section: Discussionmentioning
confidence: 99%
“…Concurrent with the decline of sea lions and expansion of groundfish fisheries in the Aleutians in the late 1970s, there was a substantial change in ocean climate and declines in the abundance of non-fished species such as capelin, skates and benthic invertebrates [ 88 ]. Thus while commercial fisheries might be evoked to partially explain the interannual fluctuations in the abundance of some species [ 89 ], the geographic and temporal coherence of the collapse of large numbers of taxa argues for a large-scale common cause such as changes in ocean climate [ 45 , 89 – 91 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most studies of the relationships of humans and ecosystems are presented in terms of human impacts on ecosystems 1 2 . However, our ability to understand and mitigate human impacts depends on research that elucidates the roles humans play in ecosystems including how they interact with other species 3 .…”
mentioning
confidence: 99%
“…In modern marine ecosystems, humans are depleting many commercial fisheries, causing major disruptions to ecosystem function and the persistence of species 1 4 5 6 7 . As a result, regulators have curtailed fisheries and excluded local peoples from traditional harvesting territories 2 . This is a critical problem for the Aleut peoples of the western Gulf of Alaska, who depend strongly on biotic resources from the marine communities 8 9 10 .…”
mentioning
confidence: 99%
“…It also showed that the Aleut were often required to respond directly to climate-driven changes in marine productivity and changes in the Aleut population correlated closely with changes in the overall productivity of the marine-scape [3,26,27]. Ecological surveys of the terrestrial and intertidal landscapes and near-shore food-web analyses show that certain components of the ecosystem, and certain species interactions, may have been a byproduct of human ecosystem engineering as the local peoples intensely harvested resources over thousands of years [3,[28][29][30]. Unexpectedly, there is no evidence that the local peoples put any harvesting pressure on key species over the last 4500 years, and no evidence of over-exploitation [31,32], although the Aleut did expand their diet breadth down the food chain during periods of decreasing marine productivity [33].…”
Section: Introductionmentioning
confidence: 99%